Wear-resistant and lubricating delta-MoN-containing molybdenum nitride-based coating as well as preparation method and application thereof

Through HiPIMS deposition technology, Cu is doped in the coating to form a δ-MoN molybdenum nitride-based coating, which solves the problem of high friction coefficient of the coating at medium temperatures and achieves wear-resistant lubricating performance in a wide temperature range. It is at medium and high temperatures where oil lubrication fails.

CN119433472AInactive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411494805.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing coatings have high friction coefficient at medium temperatures, making it difficult to develop protective coatings with wear-resistant lubrication properties in wide temperature ranges, especially at medium and high temperatures where oil lubrication failure occurs.

Method used

A δ-MoN-containing molybdenum nitride-based coating was prepared by HiPIMS physical vapor deposition method. The formation of δ-MoN and grain refinement were promoted through Cu doping to form a dense coating to improve lubricating performance.

Benefits of technology

The friction coefficient is optimized at medium and low temperatures, and a thermally stable lubricating phase MoCuO4 is formed by reaction between Cu and MoO3 at high temperatures, which significantly improves the wear-resistant lubricating performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433472A_ABST
    Figure CN119433472A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant and lubricating delta-MoN-containing molybdenum nitride-based coating as well as a preparation method and application thereof. The technological process of the preparation method comprises the following steps: S1, polishing and cleaning a substrate, and loading the substrate into a reaction chamber; s2, the reaction chamber is vacuumized and heated, and glow cleaning and ion etching are conducted on the surface of the base body; and S3, a high-power pulse magnetron sputtering MoCu target is used, and the MoN-Cu coating is deposited in the mixed atmosphere of inert gas and nitrogen. Cu is doped under the HiPIMS condition to drive delta-MoN to be formed in the coating, meanwhile, grain refinement is promoted through the high ionization rate of Cu under the HiPIMS technology, agglomeration caused by poor wettability between Cu and MoN is avoided, and the coating which is excellent in performance, smooth and compact can be obtained. Delta-MoN is more easily oxidized to form a lubricating phase, so that the dry friction coefficient of the coating at medium and low temperatures can be further optimized. And meanwhile, Cu and MoO3 form a lubricating phase MoCuO4 with better thermal stability at a higher temperature, the lubricating effect can be continuously played, and the lubricating performance of the molybdenum nitride-based coating in the dry friction process at medium and low temperatures is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and in particular to a wear-resistant and lubricating δ-MoN molybdenum nitride-based coating, a preparation method and an application thereof. Background Art

[0002] Wear is the main reason that affects the service life of parts. In order to ensure the efficient, reliable and long-life operation of parts such as aerospace, microelectronics, and automobile engine pistons, the requirements for the friction and wear performance of moving parts are becoming increasingly stringent, especially under conditions of dry friction and large fluctuations in operating temperature. With the transformation and upgrading of my country's industry, traditional oil lubrication methods have limitations in many situations. For example, in special environments such as high / low temperature alternation and high vacuum, oil lubrication is prone to failure.

[0003] For example, the mechanical and thermal loads on parts near the engine are large during operation, and thermal fatigue cracking and wear are prone to occur under such conditions; and the lubricating oil deteriorates and fails at high temperatures, which further intensifies the wear and even causes the parts to stick. Due to the extremely harsh service conditions, many engineering materials still need to maintain good mechanical properties and wear-resistant lubrication properties at 300 to 400°C to ensure reliable operation and efficient transmission. How to improve the service life and working reliability of engineering equipment at medium temperatures where oil lubrication fails seriously restricts its development.

[0004] However, low-friction DLC and MoS2 coatings are easily oxidized and decomposed at high temperatures, and the DLC film has high stress and poor film / substrate bonding, and is prone to failure under impact vibration. MoN-based self-lubricating coatings have excellent mechanical properties and chemical stability. During the friction process, they easily form a layered and easily sheared MoO3 lubricating phase, which can provide good lubrication at room temperature and high temperature. At present, wear-resistant protective coatings can easily achieve good lubrication effects at high temperatures, and molybdenum nitride-based coatings also have excellent lubrication properties at room temperature, but the friction coefficient at medium temperatures has remained high, making it difficult to develop wear-resistant and lubricating protective coatings over a wide temperature range. Summary of the invention

[0005] In order to solve at least one of the above technical problems, the present application provides a wear-resistant and lubricating δ-MoN molybdenum nitride-based coating, a preparation method and an application thereof, and the technical solution adopted is as follows.

[0006] The preparation method provided in the present application deposits a wear-resistant and lubricating δ-MoN molybdenum nitride-based coating, and the process flow of the preparation method includes:

[0007] S1, polishing and cleaning the substrate, and loading the substrate into the reaction chamber;

[0008] S2, the reaction chamber is evacuated and heated, and the substrate surface is glow cleaned and Cr ion etched;

[0009] S3, using high power pulsed magnetron sputtering MoCu target, deposited MoN-Cu coating in a mixed atmosphere of inert gas and nitrogen.

[0010] In some embodiments of the present application, during the glow cleaning process of step S2, the reaction chamber is heated to 400 to 500° C. and evacuated to 4*10 -3 Up to 7*10 -3 Pa; the temperature of the reaction chamber is adjusted to 350 to 450°C, the substrate bias is -800 to -1200V, the flow rate of the inert gas is 200 to 300sccm, and the substrate is glow cleaned for 15 to 30 minutes.

[0011] In certain embodiments of the present application, during the Cr ion etching process of step S2, the inert gas flow rate is 50 to 100 sccm, the substrate bias is -600 to -800 V, the target current is 60 to 100 A, and cathode arc evaporation Cr is used to bombard the substrate for 3 to 8 minutes.

[0012] In certain embodiments of the present application, during the ion etching process, the target-to-substrate distance is 15 to 25 cm.

[0013] In certain embodiments of the present application, in step S3, the temperature of the reaction chamber is 350 to 450°C, and inert gas and nitrogen are introduced, wherein nitrogen accounts for 30% to 60% of the total pressure of the mixed gas, the gas pressure of the reaction chamber is 0.4 to 0.8 Pa, the substrate bias voltage is -50 to -250 V, and the deposition time is 120 min.

[0014] In certain embodiments of the present application, the power of the HiPIMS power supply is 2 to 10 kW, the frequency is 200 to 500 Hz, and the pulse width is 100 to 250 us.

[0015] In certain embodiments of the present application, in step S3, the target-base distance is 8 to 12 cm.

[0016] The molybdenum nitride-based coating containing δ-MoN provided in the present application is obtained by the preparation method as described above.

[0017] In certain embodiments of the present application, the δ-MoN-containing molybdenum nitride-based coating has a Mo content of 45-60 at.%, a N content of 30-45 at.%, and a Cu content of 0-15 at.%.

[0018] The molybdenum nitride-based coating containing δ-MoN provided in the present application is applied in the field of wear resistance and protection.

[0019] This application has at least the following beneficial effects:

[0020] The present application aims to provide a nitride coating with excellent wear resistance and lubrication performance at medium and high temperatures where oil lubrication fails. The MoN-Cu coating containing δ-MoN can play a role in lubrication and friction reduction.

[0021] The present application utilizes the high ionization rate of Cu under the HiPIMS process to promote grain refinement and drive phase transformation to form δ-MoN under a small amount of Cu, and a dense coating can be obtained under the influence of two-phase competitive growth and a small amount of Cu.

[0022] In the coating of the present application, due to the easy oxidation property of δ-MoN, a friction film with lubrication and friction reduction is quickly formed, and the introduction of Cu element can form MoCuO4 which is easier to be sheared, and has better lubricity and high temperature stability, which solves the problem of easy volatility of MoO3 at high temperature. During the friction process at 400°C, the MoN coating will form an amorphous enamel oxide layer, and because of the adhesion of the oxide, the friction film formed on the surface has poor lubrication performance, and the coating has a higher friction coefficient at this temperature. The formation of δ-MoN by inducing phase transformation in the coating through Cu doping can further optimize the friction coefficient of the coating at medium and low temperatures through its rapid oxidation.

[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present application is further illustrated below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments embodied in the following drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0025] Figure 1 Schematic diagram of the target substrate during the deposition process.

[0026] Figure 2 Surface, cross-sectional morphology and EDS composition of (a) embodiment and (b) comparative example.

[0027] Figure 3 GIXRD of Examples and Comparative Examples.

[0028] Figure 4 The hardness and elastic modulus of the embodiments and comparative examples are shown in FIG.

[0029] Figure 5 The following are the scratch test results of the embodiments and comparative examples.

[0030] Figure 6 The friction coefficient curves of the embodiments and comparative examples are shown in FIG.

[0031] Figure 7 It is the average friction coefficient and wear rate of the embodiment and comparative example.

[0032] Figure 8 The wear scar cross-section curves of (a) comparative example and (b) embodiment.

[0033] Fig. 9 Raman spectroscopy analysis of the wear scar of (a) comparative example and (b) embodiment. DETAILED DESCRIPTION

[0034] The embodiments of the present application are described in detail below in conjunction with the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0035] In the description of the present application, it should be understood that the terms "center", "middle", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0036] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0037] In the description of this application, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0038] In the description of the present application, if the reference terms "as an implementation", "an embodiment", "some instances", "some embodiments", "illustrative embodiment", "example", "specific example", "some examples", etc. appear, it means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0039] The present application relates to a wear-resistant and lubricating δ-MoN-containing molybdenum nitride-based coating, which is prepared by a HiPIMS physical vapor deposition method.

[0040] The coating phase structure is mainly δ-MoN, which is easily oxidized to form a lubricating phase during the friction process, giving the coating excellent wear resistance and friction reduction properties.

[0041] The coating surface is smooth and dense, and the cross section presents an amorphous growth morphology. The content of Mo in the molybdenum nitride-based coating containing δ-MoN is 45-60at.%, the content of N is 30-45at.%, and the content of Cu is 0-15at.%. The high ionization rate of Cu under HiPIMS conditions and the solid solution of a small amount of Cu promote the grain refinement of the film and drive the formation of δ-MoN.

[0042] It should be noted that when the Cu content is less than 5 at.%, Cu mainly exists in the molybdenum nitride lattice in the form of solid solution, thus driving the formation of δ-MoN under HiPIMS conditions; when the Cu content continues to increase, Cu exists in an amorphous form at the grain boundary to form a nanocomposite structure. However, if the Cu content is too high, the mechanical and tribological properties of the coating will decrease.

[0043] The present application relates to an application of a molybdenum nitride-based coating containing δ-MoN, and the molybdenum nitride-based coating containing δ-MoN is applied in the field of wear resistance and protection.

[0044] The present application relates to a preparation method, which deposits and obtains a wear-resistant and lubricating δ-MoN-containing molybdenum nitride-based coating.

[0045] The preparation method includes the following process flow: S1, polishing and cleaning the substrate, and loading the substrate into a reaction chamber. S2, vacuumizing and heating the reaction chamber, and performing glow cleaning and Cr ion etching on the surface of the substrate. S3, using a high-power pulsed magnetron sputtering MoCu target to deposit a MoN-Cu coating in a mixed atmosphere of an inert gas and nitrogen.

[0046] It should be noted that during the glow cleaning process of step S2, the reaction chamber is heated to 400 to 500°C and evacuated to 4*10 -3Up to 7*10 -3 Pa; the temperature of the reaction chamber is adjusted to 350 to 450°C, the substrate bias is -800 to -1200V, the flow rate of the inert gas is 200 to 300sccm, the gas pressure of the reaction chamber is 2.0Pa, and the substrate is glow cleaned.

[0047] In step S2, the duration of the glow cleaning is 20 minutes.

[0048] Furthermore, during the Cr ion etching process of step S2, the inert gas flow rate is 70 sccm, the substrate bias voltage is -800 V, the target current is 60 to 100 A, and cathode arc evaporation is used to bombard the substrate with Cr.

[0049] During the ion etching process on the substrate surface, the target-substrate distance is 15 to 25 cm. If the target-substrate distance is too small, the etching will be too strong and defects will be generated on the substrate, which is not conducive to the bonding force; if it is too large, the etching effect is poor, and the contamination on the substrate surface cannot be effectively removed and the substrate cannot be activated.

[0050] In step S2, the duration of ion etching is 3 to 8 minutes.

[0051] During the coating deposition process of step S3, the temperature of the reaction chamber is 350 to 450°C, inert gas and nitrogen are introduced, wherein nitrogen accounts for 30% to 60% of the total pressure of the mixed gas, the pressure of the reaction chamber is 0.4 to 0.8 Pa, and the substrate bias voltage is -50 to -250 V. Excessive nitrogen will poison the target material, reduce the deposition rate, and even cause arcing on the target surface; too little nitrogen will cause the metal phase to appear in the prepared coating, which is not conducive to its hardness and tribological properties; too high chamber pressure is not conducive to magnetron sputtering, and will make the prepared MoN-Cu coating less dense.

[0052] The power of HiPIMS power supply is 2 to 10kW, the frequency is 200 to 500Hz, and the pulse width is 100 to 250us. The frequency and pulse width determine the duty cycle. When the duty cycle is small, the ionization rate of the particles sputtered by the target is higher, which affects the ionization rate of Cu during the thin film deposition process. When the Cu ionization rate is high, it is easier to migrate and diffuse when deposited on the substrate, so it is not easy to agglomerate, which can make the grains refined and the film dense.

[0053] In step S3, the target-substrate distance is 8 to 12 cm. If the target-substrate distance is too large, the deposition rate and the energy of the film-forming particles will be reduced. When the energy is low, the migration and diffusion of the particles will be difficult, thus reducing the density and performance of the coating. If the target-substrate distance is too small, the substrate will affect the magnetic field near the target surface, and the sharp edge of the substrate may cause arcing. Secondly, too strong bombardment will lead to more defects in the film and excessive stress.

[0054] It should be noted that the deposition time in step 3 is 120 min.

[0055] The MoCu target used in high-power pulsed magnetron sputtering is a planar target, and the Mo target has through holes for placing Cu pillars.

[0056] The inert gas used in this application is Ar.

[0057] In this application, δ-MoN is formed in the coating by doping Cu under HiPIMS conditions. At the same time, the high ionization rate of Cu under the HiPIMS process promotes grain refinement, avoids agglomeration between Cu and MoN due to poor wettability, and obtains a smooth and dense coating with excellent performance. δ-MoN is more easily oxidized to form a lubricating phase, so the dry friction coefficient of the coating at medium and low temperatures can be further optimized. At the same time, at higher temperatures, Cu and MoO3 form a more thermally stable lubricating phase MoCuO4, which can continue to play a lubricating role, effectively improving the lubrication performance of the molybdenum nitride-based coating during dry friction at medium and low temperatures.

[0058] The performance of the molybdenum nitride-based coating containing δ-MoN in the present application is described in detail below in conjunction with specific embodiments. It should be noted that the following description is only an illustrative description and is not a specific limitation to the present application.

[0059] Example

[0060] The preparation method of the molybdenum nitride-based coating containing δ-MoN includes the following process flow, and the schematic diagram of the target material and the substrate during film deposition is as follows: Figure 1 shown.

[0061] S1, vacuum the reaction chamber to 7*10 -3 Pa, after the vacuum degree reaches the set value, the Ar flow rate is set to 300sccm, the substrate surface is glow cleaned, the gas pressure of the reaction chamber is 2.0Pa, the substrate bias voltage is set to -1000V, and the duration is 20min.

[0062] S2, the temperature of the reaction chamber was adjusted to 350 °C, the Ar flow rate was adjusted to 100 sccm, the gas pressure of the reaction chamber was 0.7 Pa, the substrate was facing the Cr target, the target-substrate distance was 15 cm, the substrate bias was -800 V, the target current was 80 A, and the cathode arc evaporation Cr target was used to bombard the substrate surface for 5 min.

[0063] S3, turn on the HiPIMS power supply of the MoCu target, introduce 40sccm of Ar into the reaction chamber, introduce 60sccm of nitrogen, the gas pressure in the reaction chamber is 0.6Pa, the substrate bias is -100V, the HiPIMS power supply power is 4kW, the frequency is 300Hz, the pulse width is 150us, and the deposition time is 120min.

[0064] The MoN-Cu coating was prepared.

[0065] Comparative Example

[0066] The preparation method of the molybdenum nitride coating includes the following process flow.

[0067] R1, the reaction chamber is evacuated to 7*10 -3 Pa, after the vacuum degree reaches the set value, the Ar flow rate is set to 300sccm, the substrate surface is glow cleaned, the gas pressure of the reaction chamber is 2.0Pa, the substrate bias voltage is set to -1000V, and the duration is 20min.

[0068] R2, the temperature of the reaction chamber was adjusted to 350 °C, the Ar flow rate was adjusted to 70 sccm, the substrate was facing the Cr target, the target-substrate distance was 25 cm, the substrate bias was -800 V, the target current was 80 A, and cathode arc evaporation was used to bombard the substrate surface for 5 min.

[0069] R3, turn on the HiPIMS power supply of the Mo target, introduce 40sccm of Ar into the reaction chamber, introduce 60sccm of nitrogen, the gas pressure in the reaction chamber is 0.6Pa, the substrate bias is -100V, the HiPIMS power supply power is 2kW, the frequency is 300Hz, the pulse width is 150us, and the deposition time is 120min.

[0070] The MoN coating was prepared.

[0071] Performance Test:

[0072] The MoN-Cu coating and the MoN coating prepared in the above examples were tested, and the test method was as follows.

[0073] 1. The surface and cross-sectional morphology of the coating were analyzed by SEM (SEM; Hitachi SU8220), and EDS (EDS; Oxford Instruments X-Max N )Analyze the composition of the coating, such as Figure 2 shown.

[0074] It can be seen that the comparative example without Cu introduction presents obvious columnar crystal growth morphology, and the surface is fine columnar crystal particles. After adding Cu-3.8at.%, the example presents an amorphous growth morphology, and the surface becomes denser and smoother.

[0075] 2. XRD (GIXRD; Bruker D8 Advance) was used to analyze the phase structure of the coating. The incident angle was 1° to avoid the interference of the substrate diffraction peak on the coating. The test results are as follows: Figure 3 shown.

[0076] Compared with the comparative example, the phase structure of the embodiment after Cu doping changes significantly, forming δ-MoN with 200-plane as the preferred orientation. At the same time, due to grain refinement, the diffraction peak of fcc-Mo2N becomes significantly broadened. Grain refinement is caused by Cu doping on the one hand and competitive growth of the two phases on the other.

[0077] 3. Using nanoindentation (Anton Paar TTX-NHT 2 )Analyze the mechanical properties of the coating, such as Figure 4 shown.

[0078] Compared with the comparative example, the hardness of the embodiment is improved, but its elastic modulus is reduced, so the H / E value is larger, which indicates that its toughness is better and may also be beneficial to its wear resistance. The improvement in hardness is due to the solid solution of Cu on the one hand, and the composite of the two-phase structure on the other hand.

[0079] 4. Use the scratch test (Anton Paar Revetest scratch tester) to characterize the bonding strength between the coating and the substrate. Good bonding strength can ensure that the film can play its functions, such as Figure 5 shown.

[0080] From the scratch results, it can be seen that the Cu-doped embodiment has a better bond with the substrate, arc cracks appear inside the scratch under a larger scratch force, and continuous peeling of the film appears at the scratch edge at 86.2N.

[0081] 5. Friction coefficient test Figure 6 As shown: Under room temperature, humidity of 45% and high temperature of 400°C, the test was carried out using a ball-disc high temperature friction and wear tester (Anton Paar HT1000), the grinding ball was an Al2O3 ball, the load was 2N, and the friction radius was 2mm. Wear rate test: After friction under room temperature, humidity of 45% and high temperature of 400°C, the wear scar cross section was detected using a laser confocal microscope (Olympus OLS4100), and the wear scar volume was calculated by taking the average of the cross-sectional areas of 5 wear points, and the wear volume V was calculated by combining the formula V=A*2πr, and the wear rate was calculated by the formula W=V / (P*L), where L is the friction distance.

[0082] The average friction coefficient and wear rate of the wear-resistant lubricating coating in the embodiment and the comparative example at room temperature and 400°C are as follows: Figure 7 As shown, the friction coefficient at room temperature is 0.32 and the wear rate is 6.4×10 -8 mm 3 / (N×m), which is comparable to DLC; the friction coefficient at 400°C reaches 0.34. Compared with most coatings, the coating in the embodiment has good lubrication performance at this temperature, and the wear rate is 6.4×10 -7 mm 3 / (N×m), showing excellent wear resistance. At this temperature, the friction coefficient of the comparative example is 0.54, because the adhesion in the wear scar causes relatively small wear, and this adhesion also makes its friction coefficient higher. The introduced Cu element is also beneficial to improve adhesion during high temperature friction and also helps to reduce the friction coefficient.

[0083] After the friction test at 400℃, the wear scar cross-section curve at a certain point is as follows Figure 8 As shown, it can be seen that, compared with the film, the wear rate of the coating at this temperature is very small, showing excellent wear resistance.

[0084] 6. Raman (LabRAM HR Evolution 532nm lasers) was used to detect the oxidation products formed on the sample surface after the friction test, such as Fig. 9 shown.

[0085] It can be seen from the figure that the oxidation degree of the comparative example and the embodiment on the sample surface is roughly the same, but the oxide MoO3 formed in the wear scar of the embodiment is richer, because δ-MoN is more easily oxidized to form a lubricating phase than fcc-Mo2N, so more lubricating phases are formed under the action of tribochemical reaction.

[0086] The above is a detailed description of the implementation methods of the present application in conjunction with the accompanying drawings, but the present application is not limited to the above implementation methods. Various changes can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. A preparation method, wherein the preparation method deposits a wear-resistant and lubricating δ-MoN molybdenum nitride-based coating, characterized in that: include S1, polishing and cleaning the substrate, and loading the substrate into the reaction chamber; S2, the reaction chamber is evacuated and heated, and the substrate surface is glow cleaned and Cr ion etched; S3, using high power pulsed magnetron sputtering MoCu target, deposited MoN-Cu coating in a mixed atmosphere of inert gas and nitrogen.

2. The preparation method according to claim 1, characterized in that: During the glow cleaning process of step S2, the reaction chamber is heated to 400 to 500°C and evacuated to 4*10 -3 Up to 7*10 -3 Pa; the temperature of the reaction chamber is adjusted to 350 to 450°C, the substrate bias is -800 to -1200V, the flow rate of the inert gas is 200 to 300sccm, and the substrate is glow cleaned for 15 to 30 minutes.

3. The preparation method according to claim 2, characterized in that: During the Cr ion etching process of step S2, the inert gas flow rate is 50 to 100 sccm, the substrate bias voltage is -600 to -800 V, the target current is 60 to 100 A, and cathode arc evaporation Cr is used to bombard the substrate for 3 to 8 minutes.

4. The preparation method according to claim 3, characterized in that: During ion etching, the target-substrate distance is 15 to 25 cm.

5. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the reaction chamber is 350 to 450°C, and inert gas and nitrogen are introduced, wherein nitrogen accounts for 30% to 60% of the total pressure of the mixed gas, the gas pressure of the reaction chamber is 0.4 to 0.8 Pa, the substrate bias voltage is -50 to -250 V, and the deposition time is 120 min.

6. The preparation method according to claim 5, characterized in that: The HiPIMS power supply has a power of 2 to 10 kW, a frequency of 200 to 500 Hz, and a pulse width of 100 to 250 us.

7. The preparation method according to claim 1, 5 or 6, characterized in that: In step S3, the target-base distance is 8 to 12 cm.

8. A wear-resistant and lubricating δ-MoN molybdenum nitride-based coating, characterized in that: The molybdenum nitride-based coating containing δ-MoN is obtained by the preparation method according to any one of claims 1 to 7.

9. The wear-resistant and lubricating δ-MoN molybdenum nitride-based coating according to claim 8, characterized in that: The δ-MoN-containing molybdenum nitride-based coating has a Mo content of 45-60 at.%, a N content of 30-45 at.%, and a Cu content of 0-15 at.%.

10. An application of a molybdenum nitride-based coating containing δ-MoN, characterized in that: The molybdenum nitride-based coating containing δ-MoN as claimed in claim 8 or 9 is used in the field of wear resistance and protection.

Citation Information

Patent Citations

  • Abrasion-resistant and self-lubricating Mo-Cu-V-N composite coating and preparation method and application thereof

    CN107604329A

  • THE MoN-Cu COATING LAYER AND METHOD FOR MANUFACTURING MoN-Cu COATING LAYER

    KR1020130125663A